P744Regulation of adiponectin expression by selective molecular components of mediterranean diets in human adipocytes. (15th July 2014) - Scoditti, E; Massaro, M; Carluccio, MA; Pellegrino, M; Calabriso, N; Wabitsch, M; Storelli, C; De Caterina, R
Abstract: Purpose: Adiponectin is an adipocyte-derived hormone with insulin-sensitizing, anti-inflammatory and anti-atherogenic actions. Adiponectin levels are suppressed in obesity through mechanisms involving chronic inflammation and oxidative stress. Olive oil consumption is associated with beneficial cardiovascular and metabolic actions with contributions from the antioxidant phenol hydroxytyrosol (HT) and the monounsaturated fatty acid oleic acid (OA, 18:1n-9cis), which possess anti-inflammatory and vasculoprotective properties. We determined the effects of HT and OA, alone and in combination, on adiponectin expression in human Simpson-Golabi-Behmel syndrome adipocytes, under pro-inflammatory condition induced by the cytokine TNF-α. Methods: Adipocytes were treated with 1-50 μmol/L OA for 48 h, 0.1-10 μmol/L HT for 1 h or with a combination of OA plus HT, before 10 ng/mL TNF-α for 24 h. Adiponectin protein levels in the culture medium and mRNA expression were measured by ELISA and real-time PCR. Peroxisome proliferator-activated receptor (PPAR)Γ protein and mRNA levels, as well as PPARΓ activation, were determined by Western blotting, real-time PCR, and ELISA. Phosphorylation of c-Jun N-terminal kinase (JNK) and production of reactive oxygen species (ROS) were detected by Western blotting and the peroxide-sensitive fluorophore dichlorofluoresceine diacetate, respectively. Results: OA or HT significantly prevented, in a concentration-dependent manner, TNF-α-induced suppression of total adiponectin secretion as well as mRNA levels in human adipocytes (40% vs control for TNF-alpha, 80% vs control for TNF-alpha + HT or TNF-alpha + OA, P<0.05). HT and OA prevented - by 30% - TNF-α-induced downregulation of PPARΓ, a master transcriptional regulator of adiponectin, in association with blunted basal and TNF-α-triggered production of ROS. HT+OA co-treatment restored adiponectin and PPARΓ expression in an additive manner compared with single treatment. We also explored HT and OA effect on the mitogen-activated protein kinase JNK phosphorylation, crucial for adiponectin and PPARΓ suppression by TNF-α. Here HT or OA alone as well as OA+HT combination in an additive manner attenuated TNF-α-stimulated JNK phosphorylation. Conclusions: The virgin olive oil components, OA and HT, at nutritionally relevant concentrations, have additive effects in preventing adiponectin downregulation in inflamed adipocytes, via the attenuation of oxidative stress and JNK-mediated PPARΓ suppression. These components may explain at least part of the metabolic and vascular beneficial role of olive oil in Mediterranean diets.